2016
DOI: 10.1021/acs.analchem.6b03002
|View full text |Cite
|
Sign up to set email alerts
|

(Bio)Sensing Using Nanoparticle Arrays: On the Effect of Analyte Transport on Sensitivity

Abstract: There has recently been an extensive amount of work regarding the development of optical, electrical, and mechanical (bio)sensors employing planar arrays of surface-bound nanoparticles. The sensor output for these systems is dependent on the rate at which analyte is transported to, and interacts with, each nanoparticle in the array. There has so far been little discussion on the relationship between the design parameters of an array and the interplay of convection, diffusion, and reaction. Moreover, current me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…It can be seen that plottedi nt his manner,a ll of the data taken from FE simulations have ac lose match to the analytical solutionsf or transport to an anodisk. For nanocyliders under conditions such that Pe np < 1, numerical data were within 5% of those calculated via Equation (5). For nanorods the differen- .…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…It can be seen that plottedi nt his manner,a ll of the data taken from FE simulations have ac lose match to the analytical solutionsf or transport to an anodisk. For nanocyliders under conditions such that Pe np < 1, numerical data were within 5% of those calculated via Equation (5). For nanorods the differen- .…”
Section: Resultssupporting
confidence: 58%
“…We show that our approximation provides accurate prediction of transport to these shapes over a wide range of convective/diffusive conditions. Results from this study can be readily combined with the theory previously reported by Lynn and Homola to predict steady‐state rates of transport to arrays nanorods.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…nanoparticles is well-established today and encompasses chemical [7], photochemical [8], and biological routes [9]. The research on LSPR sensors is a very active area and nowadays encompass the optimal arrangement of gold nanostructures on sensor surfaces for providing optimal analyte transport [10,11], the combination plasmonic structures with other materials (e.g., fluorescent quantum dots for surface-enhanced fluorescence) [12], miniaturization [13], and surface-enhanced Raman spectroscopy leading to the detection of single molecules [14]. However, simple and cost-and timeefficient fabrication strategies for highly sensitive LSPR sensors utilizing shifts in the spectral position of the LSPR for signal transduction were most often fabricated by deposition of wetchemically prepared gold nanoparticles on substrate surfaces.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%